IMPLEMENTASI BUDAYA POLITIK SERTA PENGARUHNYA TERHADAP PEMBANGUNAN POLITIK - Egeten, Maxi (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: Now a days, the Indonesian political system is undergoing a process of democratization that brings consequences not only to the dynamics of national political life. Aim to find out how the implementation of cultural influences on political development. The population in this study is a community in the District Girian Bitung City. While samples taken from some community representatives, consisting of community leaders, religious leaders, youth leaders, Community Organizations by the number of samples taken in this study were 50 respondents This study is a descriptive study kuaiitatif, data obtained from the results of this study are described with words representing categories to conclude, if there is data in the form of figures will be processed based on the calculation: add up, compared with the expected number and the result diprosentasekan The results showed political cultural influences society basically make all the people to get involved in the political development and political culture of society is basically to create a civilized society Keywords: Political Culture and Political Development